Inter-fibre failure of through-thickness reinforced laminates in combined transverse compression and shear load - Cui, Hao; Melro, António R.; Yasaee, Mehdi (Elsevier, 2018)
Extensive studies have been reported on the improvement of through-thickness reinforcement to inter-laminar performance of composite laminates; current understanding on the in-plane performance is relatively limited, although it is also concerned in industrial application. The influence of through-thickness reinforcement (Z-pinning) on the inter-fibre failure in compression of unidirectional laminates was investigated. Both unpinned and Z-pinned laminates were tested at four different off-axis angles, representing different combinations of transverse compression and in-plane shear stress. It was found that the stiffness of Z-pinned laminates decreased significantly in all off-axis angles. The failure strain and strength were reduced in shear dominated failure modes, while improved in the compression dominated failure modes by the presence of the Z-pins. A further investigation on the angle of failure plane was carried out and a comparison with analytical failure models is presented.
Keywords: Z-pin; Inter-fibre failure; Strength; Fibre volume fracture